2009
DOI: 10.1142/s0217984909020710
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Synchronization of Different Dimensional Chaotic Systems Based on Parameter Identification

Abstract: This paper investigates the generalized synchronization issue for two different dimensional chaotic systems with unknown parameters. Based on Lyapunov stability theory and adaptive control theory, an adaptive controller is derived to achieve the generalized synchronization whether the dimension of drive system is greater than the one of the response system or not. Meanwhile, corresponding parameter updating laws can be obtained so as to exactly identify uncertain parameters. This technique has been successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Hence, if a matrix P can be found that satisfies (9) "t 2 (t 0 , 1), then the value function V(e, t) given by (12) satisfies the H-J-B equation in (11). In this case, the optimal control law u à o ðtÞ is obtained as (10). Moreover, since the quadratic function V(e, t) in (12) is positive, it can be chosen as a Lyapunov function candidate.…”
Section: Quadratic Optimal Synchronization Of Chaotic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, if a matrix P can be found that satisfies (9) "t 2 (t 0 , 1), then the value function V(e, t) given by (12) satisfies the H-J-B equation in (11). In this case, the optimal control law u à o ðtÞ is obtained as (10). Moreover, since the quadratic function V(e, t) in (12) is positive, it can be chosen as a Lyapunov function candidate.…”
Section: Quadratic Optimal Synchronization Of Chaotic Systemsmentioning
confidence: 99%
“…Consider the master and slave uncertain chaotic systems described in (19) and (20) with the robust control law u(t) given by (26) , where the optimal input u o (t) is specified as (10) . If the parameterâ is tuned by (29) , and there exist positive definite matrices Q = Q T and R = R T such that…”
Section: Lemmamentioning
confidence: 99%
See 1 more Smart Citation
“…Also, complete synchronization and antisynchronization have been observed, for example, in [16][17][18], and function projective synchronization has been studied in [19]. Until now, a variety of control schemes have been proposed to study the problem of chaos synchronization between different dimensional systems such as modified function projective synchronization [20], generalized matrix projective synchronization [21], generalized synchronization [22][23][24], inverse generalized synchronization [25], full state hybrid projective synchronization [26], Q-S synchronization [27], increased order synchronization [28,29], and reduced order generalized synchronization [30]. Amongst all kinds of synchronization, Q-S synchronization has been extensively considered [31][32][33][34][35][36][37][38][39], due to its universality and its great potential applications in applied sciences and engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of synchronization is to use the output of the drive system to control the response system so that the output of the response system follows the one of the drive system asymptotically. Up to now, many types of synchronization phenomena have been reported, such as generalized synchronization [4,5], adaptive synchronization [6][7][8][9], projective synchronization [10][11][12], impulsive synchronization [13], lag synchronization [14,15], and function projective synchronization [16,17]. And a wide variety of control approaches, such as backstepping design technique [18], fuzzy sliding mode control [19,20], adaptive control [21], optimal control [22], and ∞ control [23], have been proposed to synchronize chaotic systems.…”
Section: Introductionmentioning
confidence: 99%